(untitled) (American Journal of Islam and Society, 2020)
Carl Sharif El-Tobgui’s ambitious study of Ibn Taymiyya’s Darʾ taʿāruḍ al-ʿaql wa-l-naql provides a comprehensive exposition of Ibn Taymiyya’s philosophy. The work is divided into two parts, the first covering chapters 1 through 3 and the second chapters 4 through 6. Chapter one begins by providing a broad survey of the question of reason and revelation in Islam prior to Ibn Taymiyya; chapter two continues from there with a detailed introduction on Ibn Taymiyya’s life, times, and overall intellectual positioning. The third chapter carefully analyzes the thirty-eight discrete points made by Ibn Taymiyya against the “universal rule” of interpretation. The second part addresses Ibn Taymiyya’s ontology, philosophy, and epistemology (chaps. 4 and 5) as well as how Ibn Taymiyya applied his proposed reforms in these areas to the question of the divine attributes (chap. 6). The two parts of the work are preceded by prefatory content introducing readers to the Dar’ and outlining the fundamental stakes under contention in Ibn Taymiyya’s writing. The legacy of Ibn Taymiyya himself is considered in some depth in chapter two which reviews, inter alia, contemporary reception of the Shaykh al-Islam, a figure whose legacy remains a point of considerable contestation in the modern West. For some, Ibn Taymiyya remains a caricature of intractable literalism, a dogmatist who yields no ground to thoughtful theological efforts, and an unimaginative polemicist, hereas others paint a very different picture of an astute and brilliant theologian who deconstructs unchallenged orthodoxies and adheres, often at great personal cost, to a methodology that finds its origins in the life and thinking of the early community, or Salaf. Download